Disparities in Supreme Court Rulings Regarding the Liability of the Board of Directors of A Limited Liability Company in Cases of Malpractice - Erika Wulandari; Ganefi; Vidyadhara Prawiratama; Irfan Amir (NEGREI: Academic Journal of Law and Governance, 2026)
This study examines the disparity in Supreme Court rulings regarding the application of the principle of corporate director liability in medical malpractice cases. It employs a normative legal research method and a comparative study of Supreme Court Decisions No. 1001 K/Pdt/2017 and No. 1815 K/Pdt/2021. The 2017 Supreme Court decision extended liability to the parent company (PT Kosala Agung Metropolitan) due to its active involvement in supervising the hospital, whereas the 2021 decision limited liability to the operating PT and the treating physician, in this case, who served as both a director and a treating physician. Analysis indicates that the directors of the PT are not automatically liable for medical malpractice by healthcare personnel because their role is managerial, not technical-medical. However, if proven to have been negligent in supervision, establishing standard operating procedures, or ensuring legal compliance, directors may be held personally liable. This disparity in rulings creates legal uncertainty for healthcare services—whether in hospitals or clinics—as well as for directors and patients, particularly regarding the limits of directors’ personal liability. The study emphasizes the importance of establishing guidelines for Supreme Court rulings and harmonizing regulations between the Limited Liability Companies Act and the Health Act, so that the application of the principles of corporate and individual liability is more consistent, provides legal certainty, and protects patients’ rights in healthcare practice.